Nested tensions and smoothing tactics: An ethnographic examination of ambidexterity in a theatre. Issue 5 (November 2018) - Patrick, Holly
All organisations face contradictory demands, such as exploiting existing revenue sources while exploring new opportunities. The tensions of balancing these demands are largely met by employees, yet nearly all studies focus on the managerial perspective. This article uses an ethnographic study of a UK theatre to explore the experience of employees switching between exploitation and exploration in developing a play. Adopting a paradox lens, it identifies the existence of nested tensions. The organisational level is characterised by the well-studied contradiction between exploration and exploitation. Nested within this at the project level, a series of tensions are produced around resources, power, and learning. These tensions lead to an identity-based paradox for employees. They must perform well in the project to secure their ties of belonging to the organisation, but this simultaneously distances them from established expectations, weakening their ties of belonging. The article contributes to the literature on ambidexterity by illustrating the relational and emotional challenges faced by employees balancing exploitation and exploration, identifying the nested tensions involved in delivering ambidexterity, and through illustrating how employees smooth over these tensions using humour, shared vocabulary, and self-effacing language. On this basis, it argues for a practice-based view of ambidexterity as paradox.